2009
DOI: 10.1021/jf9030629
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Induction of Monoterpene Biosynthesis in Origanum × majoricum by Soil Bacteria

Abstract: Italian oregano (Origanumxmajoricum) was subjected to root system inoculation with three species of plant growth-promoting rhizobacteria (PGPRs) (Pseudomonas fluorescens, Bacillus subtilis, Azospirillum brasilense), and essential oil (EO) content and plant growth were measured. Composition of monoterpenes, a major EO component, was analyzed qualitative and quantitatively by gas chromatography. Total EO yield for plants inoculated with P. fluorescens or A. brasilense was 3.57 and 3.41 microg/mg fresh weight, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 32 publications
(42 reference statements)
4
43
1
Order By: Relevance
“…Similar findings have been obtained in inoculation trials in other aromatic plants, e.g. our studies of Origanum majoricum, O. majorana and Tagetes minuta grown in vermiculite pots and inoculated with WCS417r (Banchio et al 2010;Cappellari et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have been obtained in inoculation trials in other aromatic plants, e.g. our studies of Origanum majoricum, O. majorana and Tagetes minuta grown in vermiculite pots and inoculated with WCS417r (Banchio et al 2010;Cappellari et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…γ-terpinene showed a significant increase only in P. fluorescenstreated plants. Carvacrol showed a significant increase (~9-fold; p < 0.05) only in A. brasilense-treated plants (Banchio et al 2010). …”
Section: Italian Oregano (Origanum X Majoricum)mentioning
confidence: 90%
“…O. x majoricum contains up to 3 % volatile oils, comprising more than 35 different compounds (Tabanca et al 2004). The major EOs, accounting for~55 % of the total oil volume, are cis-and trans-sabinene hydrate, terpinene, carvacrol, and thymol (Banchio et al 2010).…”
Section: Italian Oregano (Origanum X Majoricum)mentioning
confidence: 99%
“…Myrtaceae is also interesting because to date, induction, a process that has been shown to be important in influencing terpene concentration in other species of woody plants (Banchio et al 2009;Mumm et al 2003;Phillips et al 2007) has not been demonstrated in the family (Henery et al 2008). Although Henery argued that induction might not be expected in an evergreen woody plant like Eucalyptus, there is scope for studies with other stimuli that have induced terpenes in other plants.…”
Section: Variation In Terpene Yield and Heritability Of Variationmentioning
confidence: 99%